A novel method for purification of polymerizable tubulin with a high content of the acetylated isotype - Carbajal, Agustin (2013)
Tubulin can be acetylated/deacetylated on Lys40 of the α-subunit. Studies of the post-translational acetylation/deacetylation of tubulin using biochemical techniques require tubulin preparations that are enriched in AcTubulin (acetylated tubulin) and (for comparison) preparations lacking AcTubulin. Assembly– disassembly cycling of microtubules gives tubulin preparations that contain little or no AcTubulin. In the present study we demonstrated that this result is owing to the presence of high deacetylating activity in the extracts. This deacetylating activity in rat brain homogenates was inhibited by TSA (Trichostatin A) and tubacin, but not by nicotinamide, indicating that HDAC6 (histone deacetylase 6) is involved. TSA showed no effect on microtubule polymerization or depolymerization. We utilized these properties of TSA to prevent deacetylation during the assembly–disassembly procedure. The effective inhibitory concentration of TSA was 3 μM in the homogenate and 1 μM in the subsequent cycling steps. By comparison with immunopurified AcTubulin, we estimated that ∼64% of the tubulin molecules in the three cycled preparations were acetylated. The protein profiles of these tubulin preparations, as assessed by SDS/PAGE and Coomassie Blue staining, were identical to that of a preparation completely lacking AcTubulin obtained by assembly–disassembly cycles in the absence of TSA. The tyrosination state and in vitro assembly– disassembly kinetics were the same regardless of the degree of acetylation.